2013
DOI: 10.1111/jgh.12189
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in Japanese Crohn's disease patients: Investigation of the standardized incidence ratio

Abstract: Among the cancers in CD patients in our hospital, no significant difference was seen in the risk for all cancers in comparison with the standard population. However, the risks for CRC and leukemia were significantly higher than in the standard population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…As for the risk of colorectal cancer in patients with CD, the most notable finding is that 89-100% of colorectal cancers occur in the rectum in Korea [62] and Japan [63,64] ; in contrast, only 40% of colorectal cancers in the West are rectal [65] . How can this difference be explained?…”
Section: Colorectal Cancermentioning
confidence: 99%
“…As for the risk of colorectal cancer in patients with CD, the most notable finding is that 89-100% of colorectal cancers occur in the rectum in Korea [62] and Japan [63,64] ; in contrast, only 40% of colorectal cancers in the West are rectal [65] . How can this difference be explained?…”
Section: Colorectal Cancermentioning
confidence: 99%
“…[33]. It has also been reported in Japan that the SIR for CRC is 2.79-5.8 [34,35]. Higashi et al reported that the frequency of comorbid CRC in CD from multiple facilities specialized for IBD was 3.5% (122/3454 patients), and that the 5-year survival rate of CRC was 88% in Stage I, 68% in Stage II, 71% in Stage IIIa, 25% in Stage IIIb, and 0% in Stage IV [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the most lethal long term complication of IBD is colorectal cancer (CRC), the risk of its development significantly increases in the patients of IBD. Patients with UC and CD bear an about 10-and 4-fold increased risk, respectively [1,30,31].…”
Section: Discussionmentioning
confidence: 99%